De la geometría euclidiana a las no euclidianas, en particular la hiperbólica, en educación secundaria a través de la geometría dinámica - Lugo López, Oscar Favián (Universidad Antonio Nariño, 2021)
Today's school requires teaching and learning about Euclidean and non-Euclidean geometry from the earliest educational levels. The research is carried out with the purpose of making a transition from Euclidean to non-Euclidean geometry, through constructions with a ruler and compass, with their subsequent comparison on the computer using the GeoGebra software, contributing to the characterization of geometric thinking involved, in seventh grade students from the Rodrigo Lara Bonilla school.